Uma Metodologia multicritério construtivista para a avaliação da vulnerabilidade de barragens e regiões a jusante - Baima, Sandra Keila de Oliveira (2015)
The Federal Law No. 12.334 of 20 September 2010, established the National Policy on Dam Safety (NBSP), whose goal is to establish the baseline for evaluation and monitoring of the implementation of the policy, serving as a tool to analyze your effectiveness in reducing accidents and improving the safety management of Brazilian dams. The law defined a number of instruments, security management, making them mandatory thereafter. In compliance with art. 7 of the said Act, the National Water Resources Council established from the CNRH Resolution No. 143 (10 July 2012), the classification system by risk category and potential damage associated and vessel volume. According to this resolution, certain technical characteristics of the dam and the valley downstream, should be scored to classify dams according to the risk and potential damage associated. However, this work proposes a dam classification model in vulnerable categories, based on a multi-criteria decision support methodology - MCDA (MultiCriteria Decision Aid) which is characterized by adopting a constructivist approach. The multi-criteria method adopted is the MACBETH, implemented in computer readable M-MACBETH